2021
DOI: 10.1109/mcom.001.2000593
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Time in a Robotic Swarm: A Joint View on Communications, Localization, and Sensing

Abstract: Autonomous robotic swarms are envisioned for a variety of sensing applications in space exploration, search-and-rescue and disaster management. An important capability of a swarm is sensing spatio-temporal processes such as radio wave propagation or seismic activities. The spatio-temporal properties of these processes dictate the required sensing position and time accuracy, as well as update rate. A dedicated wireless communication system needs to be jointly designed for swarm information exchange, self-locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…Sub-meter position uncertainty can be obtained even for LOFAR boxes that do not directly connected with anchors. This accuracy is at least an order of magnitude smaller than the wavelength of the low frequency signals (15 m), ergo sufficient for LOFAR mission [8]. The LOFAR signals are detected by all LOFAR boxes coherently.…”
Section: B Experimentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Sub-meter position uncertainty can be obtained even for LOFAR boxes that do not directly connected with anchors. This accuracy is at least an order of magnitude smaller than the wavelength of the low frequency signals (15 m), ergo sufficient for LOFAR mission [8]. The LOFAR signals are detected by all LOFAR boxes coherently.…”
Section: B Experimentsmentioning
confidence: 94%
“…In this paper, we have a joint look at the communication, localization, sensing and control aspects in an exploration mission, which is essential for design such an autonomous robotic network [7], [8]. Depending on the overall mission objectives, the trade-off between communication and localization determines the favorable swarm formations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the processing time between forward and backward transmission at node j is already compensated and very short, such that the impact of the relative frequency offset of the two clocks can be neglected. Otherwise, the clock behavior must be taken into account with an appropriate clock model [35]. The ranging bias is caused by varying group delays in the transmitter and receiver chains, for instance due to temperature variations of the RF components.…”
Section: Signal Modelmentioning
confidence: 99%
“…Following a similar research direction, [4] showed the optimization of the trajectory of a unmanned aerial vehicle (UAV)-radar for environment mapping and detection using a RL approach where rewards were predicted within a finite temporal horizon. Indeed, time is a key aspect for UAV networks because of their limited energy autonomy [5][6][7] and, thus, it should be properly accounted for when designing the UAV control for time-critical applications (e.g., search-and-rescue). In [5], an information-seeking algorithm is developed for extraterrestrial exploration and return-to-base application, whereas in [8,9] a similar problem is solved using RL for source localization.…”
Section: Introductionmentioning
confidence: 99%